2023
DOI: 10.3390/vaccines11030564
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Immunogenicity and Reactogenicity of Five Primary Series of COVID-19 Vaccine Regimens against Circulating SARS-CoV-2 Variants of Concern among Healthy Thai Populations

Abstract: To compare immunogenicity and reactogenicity of five COVID-19 vaccine regimens against wild-type SARS-CoV-2 and variants of concern (VoCs) among Thai populations, a prospective cohort study was conducted among healthy participants aged ≥18 years who had never been infected with COVID-19 and were scheduled to get one of the five primary series of COVID-19 vaccine regimens, including CoronaVac/CoronaVac, AZD1222/AZD1222, CoronaVac/AZD1222, AZD1222/BNT162b2, and BNT162b2/BNT162b2. Anti-receptor binding domain (an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The immune response to a vaccine varies with populations, prior antibody positivity, and the type of antibody tests used. We compared the immune response of the COVISHIELD vaccine used in India with AZD-1222, the early counterpart of COVISHIELD vaccine, administered in Germany ( 40 ), Taiwan ( 41 ) Africa ( 42 ), and Thailand ( 43 ). The tests used were pseudotype neutralization for the first three and an ELISA-based surrogate neutralization test for the fourth study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immune response to a vaccine varies with populations, prior antibody positivity, and the type of antibody tests used. We compared the immune response of the COVISHIELD vaccine used in India with AZD-1222, the early counterpart of COVISHIELD vaccine, administered in Germany ( 40 ), Taiwan ( 41 ) Africa ( 42 ), and Thailand ( 43 ). The tests used were pseudotype neutralization for the first three and an ELISA-based surrogate neutralization test for the fourth study.…”
Section: Discussionmentioning
confidence: 99%
“…In some countries, different vaccines were used depending on their availability. In Taiwan ( 41 ) and Thailand ( 43 ), mRNA vaccines performed better than AZD-1222 while though mRNA vaccines elicited higher Nab levels in Germany ( 40 ), fold reduction was high for the Beta variant and similar for the Delta variant. A two-dose regimen of the AZD1222 vaccine in South Africa did result in a lower antibody response using a live B.1.351 variant neutralization assay, and the vaccine did not show protection against mild-to-moderate COVID-19 ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some relevant studies on the mRNA vaccine against COVID-19 have been reported [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. In Korea, adverse events among healthcare workers who received all three doses of the BNT vaccine were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, ChAd-BTN induced the highest mean of neutralizing antibody (NAb-WT) against wild-type SARS-CoV-2. NAb-WT levels against the variants of interest, particularly the Omicron strain, were markedly attenuated for all vaccine regimens [ 13 ]. A cohort study on Military Health System beneficiaries in the United States compared humoral responses in participants vaccinated with SARS-CoV-2 infection or vaccine/infection combinations (“hybrid immunity”).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 65% of the world's population have completed an initial COVID-19 vaccination protocol (two doses for most vaccines, one or three doses for a few manufacturers), and only 35% have received COVID-19 vaccination booster doses [4]. Although most of the available COVID-19 vaccine regimens, both homologous and heterologous prime-boost schedules, exhibit high effectiveness in reducing infection, disease severity, hospitalization, and mortality, with favorable safety and immunogenicity profiles in healthy populations [5][6][7], the vaccine-elicited immunity is not perpetual and requires enhancement by booster vaccination to ensure the sustainability of protective immunity and improve vaccine efficacy over time [8,9].…”
Section: Introductionmentioning
confidence: 99%